Neither from words, nor from visions: understanding p-medicine from innovative treatments - Lemoine, Maël (Lato Sensu: Revue de la Société de philosophie des sciences, 2018)
Despite its vagueness Personalized, Precision, P4, P5, individualized, stratified medicine—or p-medicine in short—has become an increasingly popular term in biomedical literature. Philosophers have attempted to analyze what these various terms involve and have discussed consequences for medical practices. In this article, I argue that an important question remains unaddressed: what has made this project of p-medicine convincing to so many? My argument is that without real achievements, it would never have been. I also make the case that these achievements stem from the domain of monoclonal antibodies (mab), a new type of drug that justifies talks of personalized, precise, stratified, etc., medicine. In conclusion, while it may be possible to label any projection in the future of medicine as ‘p-medicine’, it is impossible to overlook mab-medicine as the spearhead.